From worship space to auditorium: Acoustic design and experimental analysis of sound absorption systems for the new auditorium of San Francesco al Prato in Perugia (Italy). (30th March 2022) - Buratti, C.; Belloni, E.; Merli, F.; Ambrosi, M.; Shtrepi, L.; Astolfi, A.
Highlights: Acoustic performance of S. Francesco al Prato in Perugia church (Italy) from worship to auditorium. Four experimental campaigns for the evaluation of the main acoustic indexes. Measured data were used to validate a simulation model by means of Ramsete program. Laboratory characterization of samples for the design of sound absorptive canopies. Final average Reverberation Time and C80 values are 1.96 s and −0.5 dB respectively. Abstract: In the present paper the design and the ante- and post-operam experimental analysis of the acoustic performance of the church of San Francesco al Prato in Perugia (Italy) are presented and discussed within the framework of a long process of design and construction. During its refurbishment (2012–2020) and its transformation from worship to auditorium, the authors carried out four experimental campaigns for the evaluation of the main acoustic indexes (Reverberation Time and Clarity Index). Measured data were used to validate four simulation models (one for each experimental campaign) by means of Ramsete software for the prediction of the acoustic behavior of the auditorium and for the design of the indoor finishes. A laboratory experimental campaign in a small-scaled reverberation room was carried out for the characterization and the design of the sound absorptive canopies hanged over the ceiling, which represent the acoustic "dominant" layer, especially at medium frequencies, where the room needed the most significant correction. A total number of 20 canopies (perforated resonant systems with rock wool inside) were installed, for a total surface area of about 180 m 2 ; together with the plaster and the 514 armchairs, they played an important role in reducing the Reverberation Time. The acoustic quality indexes gradually approached to their optimal values for music listening during the works period: the average Reverberation Time passes from a value of 4.56 s ante-operam to a value of 1.96 s post-operam; C80 passes from a mean value of −4 dB to about −0.5 dB. The first values are in line with the ones of other churches with the same volume found in the Literature, whereas the second ones are within the optimal ranges for music listening.